Biomechanical aspects in handball: Lower limb - Zebis, M. K.; Bencke, J. (Handball Sports Medicine, 2018)
Biomechanics is the study of movement and loading of biomechanical structures, in this case in the handball player. In other words, by using biomechanical measures, knowledge is obtained about movements and coordination of movements, i.e., technique, and the forces exerted by—or applied upon—the body during sports-specific movements. Biomechanical methods can be used to investigate performance parameters like throwing technique or jumping performance, and detailed information about the contribution of the different joints can be obtained. In injury prevention, information about loading of joints and soft tissue may be estimated during high-risk sports situations, and as such biomechanical risk factors can be identified. To counteract and control the external forces applied to the body during handball play, the muscles need to be adequately activated. During a high-risk ACL injury movement such as side cutting where numerous lower limb muscles are active at the same time, electromyography (EMG) can be used to measure neuromuscular activity and provide a proxy measure of muscle force output.